2005
DOI: 10.1590/s1679-87592005000200001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the mixed and barrier layers in the western Equatorial Atlantic

Abstract: A B S T R A C TClimate is closely related to the dynamics of the surface layer of the tropical Atlantic and the exchange between this latter and the atmosphere, and wearther forecasting will improve with increasing understanding of the processes that govern the relative distribution of thermodynamic properties of the water column. This paper focuses on the isolation of warm surface waters from the cold ones of the deep ocean by a salinity induced barrier layer (BL) in the western equatorial Atlantic (3 o S-7 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 48 publications
2
37
0
2
Order By: Relevance
“…Thus, the increased thickness of the BL appears more influenced by horizontal advection of salt than the surface freshwater balance. This conclusion was also obtained by Silva et al (2005) for the northern area of Brazil as well as by Zeng et al (2009) at the southeast of Vietnam.…”
Section: Westward Transport Of Salty Subtropical Waterssupporting
confidence: 70%
See 2 more Smart Citations
“…Thus, the increased thickness of the BL appears more influenced by horizontal advection of salt than the surface freshwater balance. This conclusion was also obtained by Silva et al (2005) for the northern area of Brazil as well as by Zeng et al (2009) at the southeast of Vietnam.…”
Section: Westward Transport Of Salty Subtropical Waterssupporting
confidence: 70%
“…Since the SBE911plus CTD has two thermometers, with an accuracy of about 0.001 • C, the error in computing Z T for a T = 0.5 • C is around 0.2% for a local Z T . Moreover, previous studies in the western tropical Atlantic also used the 0.5 • C criterion for the isothermal layer and its equivalent in density change (Silva et al, 2005), whose are found to be the most adaptable due to their robustness (Tanguy et al, 2010). When density stratification is exclusively controlled by temperature, the isothermal layer depth becomes equivalent to the mixed layer depth, and BLT = 0.…”
Section: Criteria For Determining Isothermal Mixed and Barrier Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the Amazon Shelf, due to the influences of both Para and Amazon rivers, is an unusually energetic coastal region that is subjected to strong seasonally driven forces, such as the Amazon River discharge, North Brazil Current transport, and trade-winds. Due to its proximity to the Equator, moderate along-shelf geostrophic currents may be generated by weak cross-shelf pressure gradients in the area's northern and southern regions (Silva et al, 2005). The formation and characteristics (depth and thickness) of the barrier and mixed layer vary seasonally, and a barrier layer (BL) is formed in distinct areas by different processes.…”
Section: Discussionmentioning
confidence: 99%
“…Neste sentido, Gibbs (1970), e mais recentemente Silva et al (2005a;2005b); Silva (2006), além de outros, têm demonstrado como situação extrema que a pluma d'água superficial com baixo valor de salinidade, resultante da descarga do rio Amazonas, pode atingir centenas de quilômetros da costa na porção oeste e leste do oceano Atlântico equatorial, no qual sofre deslocamento espacial e sazonal por processos advectivos (ventos e correntes). No caso da influência dos aportes continentais oriundos do Golfão Maranhense, esta pluma espalhou-se até uma distância de cerca de 85 km da costa no mês de Junho/1999,época que corresponde aos maioresíndices de precipitação na região (Fig.…”
Section: Discussionunclassified